Harakatul Qur’an Islamic Boarding School As Agent Of Social Change Informing The Character Of The Generation Of The Indonesian Nation - Yusutria Yusutria; Charles Charles; Yuherman Yuherman; Rina Febriana (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
This study aims to find out about the Harakatul Quran boarding school as an agent of social change in shaping the character of the Indonesian generation. The research method used is descriptive qualitative research. Sources of data were obtained from informants, namely founders, leaders, and teachers. Data collection is based on the results of interviews, observations, documentation. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. There are five components of the Harakatul Qu'ran Islamic Boarding School as an Islamic boarding school educational institution that is an agent of social change; five components consist of kyai, santri, dormitories, mosques, and the yellow book. Pondok Pesantren Harakatul Qu'ran is an agent of social change in shaping the character of the nation's generation because it has values that are full of the meaning of